SITEM INFORMASI GEOGRAFIS UNTUK LOKASI DAN ALOKASI KAWASAN PERMUKIMAN DI DAERAH ALIRAN SUNGAI (DAS) CILIWUNG HULU KABUPATEN BOGOR - Indarti Komala Dewi; Surjono H sutjahjo; Kholil Kholil; Hadi susilo Arifin (Ilmu Komputer, FMIPA, Universitas Pakuan, 2010)
Geografic Information System (GIS) is able to support strategic spatial planning proces with several ways. Its able to capture, storage, retreieval, analyse and display of spatial data or information defined by its location. various studies have been reported the application og GIS to evaluate land used planning. In these case, GIS was applied to define location and allocationsuitable area for settlement. Ciliwung watershed is one of several critical watersheds in west java province. Degradation of the the upper stream of the wtersheed functions was caused by land use changed from forest or agriculture land to settlement utilzation. These condition caused carryng capacity of upper stream af the watershed. The objective of the research is to asess suitable area for settlement in the upper stream of ciliwung watershed. Research method use GIS for analysis of suitable area for settlement. The result of the research was showed that suitable area for settlement is 19, 89 % of the upper stream of Ciliwung watershed area.Key word:, Ciliwung, GIS, Settlement, Watershed.